Isolasi dan Karakterisasi Bakteri Asam Laktat pada Usus Ayam Broiler - Meisji Liana Sari; Arfan Abrar; Merint Merint (Agricultural Faculty, 2013)
The isolated and characteristiclactic acid bacteriain broilers intestineABSTRACT. The objective of the research was to evaluate and characterize of a Lactic Acid Bacteria isolated frombroilers small intestine. The research was done by three steps : (1) Isolated Lactic Acid Bacteria, (2) Gram colourize and microscopic observation and (3) Inhibitory test with pathogen bacteria. The isolation of lactic acid bacteria was proceed by clone from broilers small intestine with MRS Broth for 24 hours, thinned until 10 9with serial number, invested in MRS jell, purify by streak plate method and storage the lactic acid bacteria in an MRS angle jell. Gram colourize was done with crystal violet liquid, Iodium, Alkohol 95% and Safranin, and also microscopic observation was done by electron microscope with 40 zooming. Inhibitory test with pathogen bacteria was evaluated with Escherichia coli as testing bacteria in 2, 4, 6, 8, 10, 12, 24 dan 48 hours incubation period.The isolation result showed two sample of isolate (A1 dan A2) and consist of the observation in shape as well as colour of the bacteria growth, for sample of isolate A1 the colonies had coccus and white colour. The isolate of A2 had sarcinar. After that, gram colouring was done and microscopic observation were identified into gram-negative bacteria became bacill and bacill cocco. Inhibitory test with pathogen bacteria showed that it produced antimicrobial with 11 mm clearing zone diameter. The result of the research got Lactobacillus sp as the genera of Lactic Acid Bacteria.